"Girls can't play": The effects of stereotype threat on females' gaming performance. (June 2016) - Kaye, Linda K.; Pennington, Charlotte R.
Abstract: The current study examined the impact of stereotype threat on female online gamers' performance and further examined whether manipulating the availability of multiple social identities effectively eliminated these performance decrements. Further, participants' implicit attitudes towards female online gamers were assessed. Eighty-one participants (60 female) were assigned to one of four experimental conditions: 1), stereotype threat, 2), multiple social identities, 3), female control, and 4), male control. They completed an Implicit Association Test and a gaming task. The number of coins collected in a 5-min time period provided a measure of gameplay performance. Results indicated that stereotype threatened females underperformed on the gaming task relative to males in the control condition. The intervention of multiple social identities successfully protected females' gameplay performance from stereotype threat. Additionally, differences were found between conditions in implicit attitudes pertaining to gender-gaming competence. This research highlights the harmful effects of negative stereotypes on females' gaming performance, and suggests that these decrements may be eliminated when females identify with an alternative positive social identity. Highlights: Assessing stereotype threat in the previously unexplored context of digital gaming. Stereotype-threatened females underperform in gameplay relative to control condition. Evidence of the multiple social identities framework as protective against threat.